Pressure generation under deformation in a large-volume press - Wang, Saisai; Zhao, Xinyu; Hu, Kuo; Feng, Bingtao; Hou, Xuyuan; Zhang, Yiming; Liu, Shucheng; Shang, Yuchen; Liu, Zhaodong; Yao, Mingguang; Liu, Bingbing (Chinese physics B, 2024)
Deformation can change the transition pathway of materials under high pressure, thus significantly affects physical and chemical properties of matters. However, accurate pressure calibration under deformation is challenging and thereby causes relatively large pressure uncertainties in deformation experiments, resulting in the synthesis of complex multiphase materials. Here, pressure generations of three types of deformation assemblies were well calibrated in a Walker-type large-volume press (LVP) by electrical resistance measurements combined with finite element simulations (FESs). Hard Al 2 O 3 or diamond pistons in shear and uniaxial deformation assemblies significantly increase the efficiency of pressure generation compared with the conventional quasi-hydrostatic assembly. The uniaxial deformation assembly using flat diamond pistons possesses the highest efficiency in these deformation assemblies. This finding is further confirmed by stress distribution analysis based on FESs. With this deformation assembly, we found shear can effectively promote the transformation of C 60 into diamond under high pressure and realized the synthesis of phase-pure diamond at relatively moderate pressure and temperature conditions. The present developed techniques will help improve pressure efficiencies in LVP and explore the new physical and chemical properties of materials under deformation in both science and technology.